Hepatoprotective Activity of Superliv Liquid and Repchol in CCl4 Induced FLKS Syndrome in Broilers - Sonkusale, P.; Bhandarker, A.G.; Kurkare, N.V.; Ravikanth, K.; Maini , S.; Sood, D. (International Journal of Poultry Science, 2010)
A 6 week long experimental trial was conducted to study whether the supplementation of herbal products Superliv liq. and Repchol (supplied by M/S Ayurvet Limited, Baddi, India) are efficacious in treatment of liver and kidney due to CCl4. A total of 75 Cobb day old broilers were divided into three equal groups (n = 25). Group A served as negative control, group B (positive control) and C (treatment group) were induced with FLKS with CCL4 @1 ml/kg body weight orally, administered every 3rd day during 15-28 days of trial. Treated group C were given Superliv Liq. @5 ml/100 chicks/day for first 2 weeks and @ 10 ml/100 chicks/day for 3-6 weeks along with drinking water in combination with Repchol@500 gm/ton of feed from 0-6 weeks. Fatty liver and kidney syndrome lead to depression in growth rate, lowered feed efficiency and disturbances in immunopathological and biochemical parameters. Final mean body weight of group C was significantly (p